2021
DOI: 10.7554/elife.66686
|View full text |Cite
|
Sign up to set email alerts
|

Insula to mPFC reciprocal connectivity differentially underlies novel taste neophobic response and learning in mice

Abstract: To survive in an ever-changing environment, animals must detect and learn salient information. The anterior insular cortex (aIC) and medial prefrontal cortex (mPFC) are heavily implicated in salience and novelty processing, and specifically, the processing of taste sensory information. Here, we examined the role of aIC-mPFC reciprocal connectivity in novel taste neophobia and memory formation, in mice. Using pERK and neuronal intrinsic properties as markers for neuronal activation, and retrograde AAV (rAAV) co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 89 publications
1
17
0
Order By: Relevance
“…The INS as a whole has classically been involved in taste learning (Yiannakas & Rosenblum, 2017) and the encoding of conditioned taste aversion (Sano et al, 2014), but has also been been implicated in recent CFC recall (Alves et al, 2013) as well as in auditory fear memory extinction (Klein et al, 2021). The INS to mPFC reciprocal connectivity has only been investigated in the context of taste learning, where it was recently found necessary for the expression of novel taste aversion (Kayyal et al, 2021). However, a direct role of INS input to PL during fear memory consolidation has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…The INS as a whole has classically been involved in taste learning (Yiannakas & Rosenblum, 2017) and the encoding of conditioned taste aversion (Sano et al, 2014), but has also been been implicated in recent CFC recall (Alves et al, 2013) as well as in auditory fear memory extinction (Klein et al, 2021). The INS to mPFC reciprocal connectivity has only been investigated in the context of taste learning, where it was recently found necessary for the expression of novel taste aversion (Kayyal et al, 2021). However, a direct role of INS input to PL during fear memory consolidation has not been described before.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that information flow between AI and RSC may rely on one or more intermediary nodes in the mPFC. Indeed, rodent tract-tracing studies reveal that the AI is connected to Cg and PrL (17, 19, 63, 67), which in turn are connected to the RSC via the cingulum bundle (63). The PrL is also directly connected to Cg, and given that RSC has relatively dense connectivity with Cg compared to other prefrontal regions, a multi-node pathway for information flow from AI→PrL→Cg→RSC is also plausible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effect was not likely due to cells merely dropping out of the imaging field of view with time, as active cell number remained stable across an identical number of pre-taste days in which mice only drank water. Prior immunocytochemical studies reported reduced numbers of activated neurons (i.e., c-Fos or pERK expression) in animals consuming familiar tastes versus novel tastes (Lin et al, 2012;Bamji-Stocke et al, 2018;Kayyal et al, 2021). In each of these studies, the familiar condition was achieved by allowing animals 6 or more days of exposure prior to perfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively few studies have explored the neural correlates of taste familiarization, and those have reported somewhat conflicting results. Expression of neuronal activity markers such as the immediate early gene c-Fos, or pERK (phosphorylated extracellular regulated kinase), is increased in GC and other taste-related forebrain areas following exposure to novel taste stimuli and subsequently decreases with repeated experience (Koh et al, 2003; Lin et al, 2012; Bamji-Stocke et al, 2018; Kayyal et al, 2021). In contrast, a study of multiunit activity in the GC in rats actively sampling a taste stimulus over several days found that the average response to the stimulus actually increased as the taste became familiar, although this change was only apparent in the late phase of the response (Bahar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%